Strategi Guru dalam Implementasi Kurikulum Merdeka pada Mata Pelajaran IPAS Kelas IV di SD - Pramulia, Fuji; Yantoro, Yantoro; Pamela, Issaura Sherly (Universitas Batanghari Jambi, 2026)
This research aims to analyze and describe Class IV Teacher Strategies in Implementing the Independent Curriculum in Natural and Social Sciences (IPAS) Learning in Elementary Schools. The method used is a qualitative approach with a type of phenomenology. This research was conducted at SD Negeri 42/IV Jambi. The data in this research is in the form of a description of the teacher's strategy in implementing the independent curriculum in grade IV science and science subjects in elementary school which was obtained through interview methods and observation as the main data and document study as research supporting data. The research subject was the class IVA teacher at SDN 42/IV Jambi. Data was collected and analyzed qualitatively. The results of the research show that the teacher's strategy at the planning stage is that the teacher creates an open module containing TP and ATP which refer to the CP provided by the center, prepares learning media, LKPD and evaluation instruments and for the implementation stage the teacher applies teaching tools that have been designed and developed In learning activities, it also includes implementing differentiated strategies, creating a conducive classroom environment and conducting learning assessments. In the evaluation stage, the teacher evaluates the strategies that have been used. The research results show that teachers use various strategies in three main stages, namely planning.